CRM (customer relationship management) applications in the Greek mobile telephony companies: a comparative analysis - Μπλέρη, Ε.; Μιχαλακοπούλου, Μ. (SPOUDAI Journal of Economics and Business, 2006)
In today's constantly changing and very competitive marketplace companies have realized that customer service is a very important factor for their success. Customer Relationship Management (CRM), is a strategy that can help companies to build long lasting relationships with their customers, achieve customer loyalty and increase their profits. CRM is a combination of methodology, software and technologies and if it is adopted effectively it can offer value to the customer and to the company. The International market of CRM is continuously growing and Greece is following this growth. Greek companies have recognized the need to adopt customer focused strategies and systems, however, the percentage of Greek companies that have implemented at least one CRM application is still low. CRM is applied in many sectors, among which, is the Telecommunications sector where it is of strategic importance. In this research paper the adoption of CRM systems by two Greek the problems and the benefits are analyzed and presented. JEL Classification: M10